The Tradition of Pilgrimage to the Tomb of Sheikh Ibrahim Mufti: A Phenomenological Study of Islamic Communities in Indonesia - Guslianto, Guslianto; Yulianti, Fadila; Utami, Elisa; Elfita, Yuni (International Journal of Multidisciplinary Research of Higher Education, 2020)
Scholars or significant religious figures who are in an area has an important role in a community, even though they have passed away, their services are still remembered and eternal in a society where the application can be done by coming on a pilgrimage to his grave to pray that all his sins are forgiven, and accepted by Allah SWT, which for the local community is also called tradition. The tradition of visiting graves has become a habit for the community, in its application by reciting tahlil, blessings, or surah found in the alquran to remind someone of death and get closer to God. Therefore it is necessary to do research so that the implementation is in accordance with what has been prescribed. This study aims to analyze and describe the implementation of the grave pilgrimage tradition at the tomb of Sheikh Ibrahim Mufti. This type of research uses qualitative research methods with a phenomenological approach. Sources of data were obtained from 10 informants by conducting direct and in-depth interviews supported by photo documentation in the study. Informants in this study were the local community, tomb keepers, surau caretakers, and pilgrims at the tomb of Sheikh Ibrahim Mufti. The results of this study indicate that: the implementation of the grave pilgrimage at the tomb of Sheikh Ibrahim Mufti, based on interview results, is in accordance with the procedures for implementing Islamic law by obtaining three findings on implementation themes, and four themes of educational values, namely spiritual, social, cultural, and disciplinary values.